An Automatic Rice Threesting Machine For Fast Filterization - Pristisal Wibowo (SEAN Institute, 2023)
For farmers, good quality and clean rice is their selling point. Automatic rice threshing machines are a new breakthrough that can be offered to them. This machine has adopted energy-saving technology and is very practical in operation. One of the technologies is a filterization system, this system is a separator between clean rice and rice grain, so that the quality of the clean rice produced will increase. By controlling the motor speed in this system, less power is used so it will be more energy efficient. This system is supported by other devices in the form of a Proximity Sensor, ATmega 2560 Microcontroller and Dimmer. So this system runs automatically based on the falling rice debit.